Ultramini-percutaneous nephrolithotomy combined with flexible ureteroscopic lithotripsy for the treatment of complex renal calculi: a clinical study - Zhu, Fuyong; Wang, Chengjun (Frontiers in Surgery, 2026)
PurposeTo compare the perioperative efficacy and safety of ultramini-percutaneous nephrolithotomy (ultramini-PCNL) combined with flexible ureteroscopic lithotripsy (FURL) vs. standard-channel PCNL in patients with complex renal calculi, with a focus on evaluating the impacts of the two procedures on postoperative oxidative stress responses, inflammatory factor levels, and renal hemodynamic parameters.MethodsA retrospective analysis was conducted on the clinical data of 135 patients with complex renal calculi admitted to our hospital from January 2023 to December 2024. According to different surgical approaches, the patients were divided into a study group (SG, n = 72) and a control group (CG, n = 63). The CG underwent standard-channel PCNL, while the SG received ultramini-PCNL combined with FURL. Surgical parameters, pain conditions, stone-free rate, oxidative stress markers, inflammatory factors, renal function, renal blood flow levels before and after surgery, as well as postoperative complications, were compared between the two groups.ResultsCompared with the CG, perioperative blood volume, time to out of bed activity and hospital stay were shorter in the SG (P < 0.05); Postoperative pain scores were lower in the SG than in CG at 12 h, 24 h and 72 h (P < 0.05), postoperative stone-free rate was higher in the SG (P < 0.05); Postoperative Cor and MDA levels were lower while SOD levels were higher in SG (P < 0.05); Postoperative CRP, IL-6 and the complication rate were lower in SG than in CG (P < 0.05). Postoperatively, compared with the preoperative values, both groups showed slight fluctuations in serum urea and creatinine (Cr) levels; however, the differences were not statistically significant (P > 0.05). After surgery, the renal artery Vmax in the SG was significantly higher than that in the CG (P < 0.05). No significant differences were observed between the two groups regarding the RI index (P > 0.05).ConclusionUltramini-PCNL combined with FURL demonstrates superior efficacy in the treatment of complex renal calculi. This approach effectively improves stone-free rate, reduces stress responses, ameliorates inflammatory factor levels, and provides a high level of safety, supporting its broader clinical application.